2023
DOI: 10.14309/ajg.0000000000002192
|View full text |Cite
|
Sign up to set email alerts
|

Early Antibody Dynamics in a Prospective Cohort of Children At Risk of Celiac Disease

Abstract: The purpose of this study was to identify possible serum biomarkers predicting celiac disease (CD) onset in children at risk. METHODS:A subgroup from an ongoing, international prospective study of children at risk of CD was classified according to an early trajectory of deamidated gliadin peptides (DGPs) immunoglobulin (Ig) G and clinical outcomes (CD, potential CD, and CD autoimmunity). RESULTS:Thirty-eight of 325 children developed anti-tissue transglutaminase IgA antibody (anti-tTG IgA) seroconversion. Twen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 12 publications
0
4
0
1
Order By: Relevance
“…In our case, a slight positivity of anti-DGP was found with a low title as the only autoantibody of CD. Anti-DGP positivity is recognized in some CD cases with a negative TTG IgA testing and normal IgA [ 77 ] and can represent an early preclinical biomarker predicting CD onset [ 78 ]. Moreover, anti-DGP have potential advantages over other conventionally used assays in milder forms of enteropathy associated with gluten-sensitive skin disorder and have been detected more frequently and at higher serum concentrations in patients with autoimmune skin disorders compared to healthy controls [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our case, a slight positivity of anti-DGP was found with a low title as the only autoantibody of CD. Anti-DGP positivity is recognized in some CD cases with a negative TTG IgA testing and normal IgA [ 77 ] and can represent an early preclinical biomarker predicting CD onset [ 78 ]. Moreover, anti-DGP have potential advantages over other conventionally used assays in milder forms of enteropathy associated with gluten-sensitive skin disorder and have been detected more frequently and at higher serum concentrations in patients with autoimmune skin disorders compared to healthy controls [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to medical care, the extremes of age also bring cost and healthcare delivery concerns, which several of our published articles focus upon (5,10,11). Finally, GI conditions unique to extremes of age need further ongoing research (12–15). We hope that this special issue will serve as a call to action to better understand the unique care of individuals in the extremes of age with GI disorders.…”
Section: Focus On Challenges In Gi Care At the Extremes Of Agementioning
confidence: 99%
“…Different gut microbial communities between DQ2− and DQ2+ celiac patients have been found, with a prevalence of Bacteroidetes and Enterococcus and a decreased number of Clostridium perfrigens, Parabacterioidetes, and Veillonella in high-profile genetic-risk children. However, some studies have reported on the influence of the type of feeding and early antibiotic exposure on the modulation of the gut microbiota and the subsequent predisposition to develop CD [10][11][12]. Patients who underwent a gluten-free diet (which is associated with different microbiota in fecal samples) had a lower immune stimulatory effect on blood-mononuclear cells compared with patients on a regular gluten diet [1,5].…”
Section: Introductionmentioning
confidence: 99%